Preparation method and application of Al-doped CuO nanosheet electrocatalyst

By preparing an Al-doped CuO nanoflake electrocatalyst, the selectivity and stability problems in the process of reducing ammonia by electrocatalyzed nitrate, and the effect of efficient ammonia production under normal temperature and pressure was achieved.

CN119824460AActive Publication Date: 2025-04-15BEIJING UNIV OF CHEM TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510282850.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-11
Publication Date
2025-04-15
Estimated Expiration
2045-03-11

Smart Images

  • Figure CN119824460A_ABST
    Figure CN119824460A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of an Al-doped CuO nanosheet electrocatalyst, and belongs to the technical field of preparation of electrocatalytic synthesis ammonia catalysts. According to the method, through an in-situ growth mode, aluminum is doped into copper oxide, and meanwhile, the morphology of the copper oxide is changed through a Joule heat method, so that the copper oxide is in a nano-sheet flower shape; specifically, firstly, copper hydroxide is prepared, then aluminum salt is used as a precursor liquid, and aluminum is loaded on the surface of the copper hydroxide; and then preparing the Al-doped CuO nano-sheet flower catalyst material through a Joule heat device. According to the invention, aluminum is doped with CuO, and the morphology of the catalyst is also changed, so that the electro-catalytic performance of the catalyst is greatly improved. The electrocatalyst prepared by the invention shows optimal performance in 0.1 mol / L N03 <-> alkaline solution under-0.635 V vs.RHE, and the Faraday efficiency of 95.7% and the ammonia yield of about 60 mg h <-1 > cm <-2 > can be realized. The prepared electrocatalyst is simple, convenient and low in cost, and the obtained material has good performance of electrocatalytic nitrate reduction synthesis of ammonia.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high-efficiency electrocatalytic reduction nitrate catalyst synthesis, and in particular to a preparation method and application of an Al-doped CuO nanosheet electrocatalyst. Background Art

[0002] Ammonia (NH3) is considered to be a promising energy carrier and is expected to play a very important role in future energy solutions. At the same time, NH3 is an important raw material for the synthesis of agricultural fertilizers, chemical compounds and other nitrogen-rich products. At present, the world's synthetic ammonia is mainly achieved by the Harber-Bosch process, but the process still faces some challenges: harsh conditions (high temperature of 350~550℃ and high pressure of 150~350 atm (1 atm=105 Pa)) are required to drive nitrogen (N2) and hydrogen (H2) to react. In addition, the Haber-Bosch process consumes a large amount of fossil fuels and emits a large amount of greenhouse gases. Its nitrogen source recovery rate is only about 50%, which not only causes a large amount of energy waste, but also leads to serious environmental problems.

[0003] Electrocatalytic synthesis of NH3 has become a research hotspot as a promising alternative. - The reduction reaction (NO3RR) can use electrical energy to synthesize NH3 under ambient conditions. It can solve the pollutants in wastewater while producing high-value-added NH3 products and realize the green nitrogen cycle. Therefore, the research on NO3RR catalysts is also a hot topic now.

[0004] It is generally believed that the initial NO3 - Reduction to NO2 - It is the main obstacle to NO3RR in most metal catalyst systems. In addition, competitive hydrogen evolution also occurs simultaneously with the nitrate reduction process. Therefore, in order to develop electrocatalytic nitrate reduction to ammonia technology, it is urgent to have a catalytic electrode with high selectivity and high stability to generate ammonia. Summary of the invention

[0005] In order to solve the technical problems raised in the background technology, the present invention provides a method for preparing an Al-doped CuO nanosheet electrocatalyst to improve the selectivity and stability of electrocatalytic generation of ammonia.

[0006] The present invention is implemented by the following technical scheme: A method for preparing Al-doped CuO nanosheet flower electrocatalyst comprises the following steps:

[0007] Step 1: ultrasonically clean the copper foam in hydrochloric acid, ethanol and water respectively, and finally dry it in a vacuum drying oven for later use;

[0008] Step 2: Soak the cleaned copper foam in a mixed solution of sodium hydroxide and ammonium persulfate to obtain copper hydroxide;

[0009] Step 3: Soak the copper hydroxide prepared in step 2 in an aluminum salt solution, and take it out and dry it naturally after a period of time;

[0010] Step 4: Place the dried material on a graphite plate and heat it with a Joule heat device to obtain an Al-doped CuO nanosheet catalyst.

[0011] Specifically, in step 1, the concentration of the dilute hydrochloric acid solution is 1-2 mol L -1 The ultrasonic time is 15-20 min. The preferred hydrochloric acid concentration is 1 mol L -1 .

[0012] Specifically, in step 2, the concentration of the mixed solution of sodium hydroxide and ammonium persulfate is 1 mol L -1 Sodium hydroxide and 0.1 mol L -1 Ammonium persulfate. The immersion time of the copper foam in the mixed solution of sodium hydroxide and ammonium persulfate is 15-30 min. Preferably, the immersion time of the copper foam is 20 min.

[0013] Specifically, the aluminum salt in step 3 is one of aluminum nitrate, aluminum sulfate, aluminum chloride, and aluminum oxide. Preferably, the aluminum salt is aluminum nitrate. The concentration of the aluminum salt solution is 0.5 mM, and the copper hydroxide immersion time is 10-30 min; preferably, the immersion time is 20 min.

[0014] Specifically, in step 4, the Joule heating temperature is 700-900°C, the voltage is set to 20 V, the current is set to 200-250 A, and the duration is 3-8 s. Preferably, the Joule heating temperature is 800°C, the voltage is set to 20 V, the current is set to 250 A, and the duration is 5 s.

[0015] One purpose of the present invention is to prepare an Al-doped CuO nanosheet catalyst, which is prepared by the above-mentioned preparation method.

[0016] Another object of the present invention is the application of the catalyst: the catalyst is used for electrocatalytic nitrate reduction to synthesize ammonia, and electrocatalytic nitrate reduction to produce ammonia at normal temperature and pressure.

[0017] The obtained Al-doped CuO nanosheet flower electrocatalyst can achieve an ampere-level current density when used for electrocatalytic nitrate reduction to produce ammonia, and also shows excellent Faraday efficiency and ammonia yield; further, the preparation method of the Al-doped CuO nanosheet flower electrocatalyst is simple, the cost is low, and the use of Joule heat not only adjusts the microscopic morphology of CuO, but also can speed up the material preparation time, greatly saving time cost, and the doping of Al also changes its internal electronic structure, greatly improving the technical effect of nitrate production of ammonia. The present invention has the following excellent effects: an Al-doped CuO nanosheet flower electrocatalyst and a preparation method thereof, firstly, cutting the foam copper and soaking it in a mixed solution of sodium hydroxide and ammonium persulfate, during which the copper on the foam copper will be oxidized to copper hydroxide, and then soaking the copper hydroxide in an aluminum salt solution, and finally placing the material on a graphite plate and heating it with a Joule heating device to obtain the Al-doped CuO nanosheet flower electrocatalyst material.

[0018] The Al-doped CuO nanosheet electrocatalyst material can achieve an ampere-level current density when used for electrocatalytic nitrate reduction to produce ammonia. It also exhibits excellent Faradaic efficiency and ammonia yield, achieving a Faradaic efficiency of 95.7% and a yield of about 60 mg h at -0.635 V vs. RHE. -1 cm -2 ammonia yield.

[0019] The preparation method of the nanosheet flower electrocatalyst material has low cost and short preparation time, and it can be expected to have good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0021] Figure 1 This is the XRD diagram of the Al-doped CuO nanosheet electrocatalyst material prepared in Example 2.

[0022] Figure 2 This is the SEM image of the Al-doped CuO nanosheet electrocatalyst material prepared in Example 2.

[0023] Figure 3 This is the TEM image of the Al-doped CuO nanosheet electrocatalyst material prepared in Example 2.

[0024] Figure 4 This is the XPS graph of the Al-doped CuO nanosheet electrocatalyst material prepared in Example 2.

[0025] Figure 5 It is a LSV comparison diagram of the Al-CuO material prepared in Example 2 and the CuO material prepared in Comparative Example 1.

[0026] Figure 6 This is a diagram of the Faraday efficiency and ammonia yield of the Al-doped CuO nanosheet electrocatalyst material prepared in Example 2. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present invention will be described clearly and completely below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] The embodiment of the invention discloses a preparation method and application of an Al-doped CuO nanosheet flower electrocatalyst.

[0029] In order to better understand the present invention, the present invention is further specifically described below through the following examples, but it should not be understood as a limitation of the present invention. Some non-essential improvements and adjustments made by technicians in this field based on the above invention content are also considered to fall within the protection scope of the present invention.

[0030] The technical solution of the present invention will be further described below in conjunction with specific embodiments.

[0031] Example 1

[0032] (1) Take 41.67 mL of concentrated hydrochloric acid and add deionized water to make up to 500 mL to obtain 1 M hydrochloric acid.

[0033] (2) Cut 2*3 cm copper foam into pieces and ultrasonically clean them in 1 M hydrochloric acid, ethanol, and deionized water for 15 min respectively. Finally, dry them in a vacuum drying oven at 60 °C for later use.

[0034] (3) Weigh 20 g of sodium hydroxide and add it to an appropriate amount of deionized water. After the sodium hydroxide is completely dissolved, transfer the solution to a 500 mL volumetric flask and make up the volume to the 500 mL mark with deionized water to obtain a 1 M sodium hydroxide solution.

[0035] (4) Weigh 0.4564 g of ammonium persulfate, pipette 20 mL of 1 M sodium hydroxide solution and add it to dissolve it by ultrasonication. After dissolution, soak the cleaned copper foam in it for 20 min to obtain blue copper hydroxide.

[0036] (5) Wash the generated copper hydroxide: Wash repeatedly with deionized water. Prepare 20 mL of 0.5 mM aluminum nitrate solution, soak the washed copper hydroxide in the aluminum nitrate solution for 10 min, and then dry the material naturally after soaking.

[0037] (6) Place the dried material on a graphite plate and set the Joule heating program: the voltage is set to 20 V, the current is set to 250 A, the duration is set to 5 s, and the temperature is set to 800 °C. After Joule heating, Al-doped CuO nanosheet material can be obtained.

[0038] Example 2

[0039] (1) Take 41.67 mL of concentrated hydrochloric acid and add a certain amount of deionized water to 500 mL to obtain 1 M hydrochloric acid.

[0040] (2) Cut 2*3 cm copper foam into pieces and ultrasonically clean them in 1 M hydrochloric acid, ethanol, and deionized water for 15 min respectively. Finally, dry them in a vacuum drying oven at 60 °C for later use.

[0041] (3) Weigh 20 g of sodium hydroxide and add it to an appropriate amount of deionized water. After the sodium hydroxide is completely dissolved, transfer the solution to a 500 mL volumetric flask and make up the volume to the 500 mL mark with deionized water to obtain a 1 M sodium hydroxide solution.

[0042] (4) Weigh 0.4564 g of ammonium persulfate, pipette 20 mL of 1 M sodium hydroxide solution and add it to dissolve it by ultrasonication. After dissolution, soak the cleaned copper foam in it for 20 min to obtain blue copper hydroxide.

[0043] (5) Wash the generated copper hydroxide: Wash repeatedly with deionized water. Prepare 20 mL of 0.5 mM aluminum nitrate solution, soak the washed copper hydroxide in the aluminum nitrate solution for 20 min, and then dry the material naturally after soaking.

[0044] (6) Place the dried material on a graphite plate and set the Joule heating program: the voltage is set to 20 V, the current is set to 250 A, the duration is set to 5 s, and the temperature is set to 800 °C. After Joule heating, Al-doped CuO nanosheet material can be obtained.

[0045] Example 3

[0046] (1) Take 41.67 mL of concentrated hydrochloric acid and add a certain amount of deionized water to 500 mL to obtain 1 M hydrochloric acid.

[0047] (2) Cut 2*3 cm copper foam into pieces and ultrasonically clean them in 1 M hydrochloric acid, ethanol, and deionized water for 15 min respectively. Finally, dry them in a vacuum drying oven at 60 °C for later use.

[0048] (3) Weigh 20 g of sodium hydroxide and add it to an appropriate amount of deionized water. After the sodium hydroxide is completely dissolved, transfer the solution to a 500 mL volumetric flask and make up the volume to the 500 mL mark with deionized water to obtain a 1 M sodium hydroxide solution.

[0049] (4) Weigh 0.4564 g of ammonium persulfate, pipette 20 mL of 1 M sodium hydroxide solution and add it to dissolve it by ultrasonication. After dissolution, soak the cleaned copper foam in it for 20 min to obtain blue copper hydroxide.

[0050] (5) Wash the generated copper hydroxide: Wash repeatedly with deionized water. Prepare 20 mL of 0.5 mM aluminum nitrate solution, soak the washed copper hydroxide in the aluminum nitrate solution for 30 min, and then dry the material naturally.

[0051] (6) Place the dried material on a graphite plate and set the Joule heating program: the voltage is set to 20 V, the current is set to 250 A, the duration is set to 5 s, and the temperature is set to 800 °C. After Joule heating, Al-doped CuO nanosheet material can be obtained.

[0052] Example 4

[0053] (1) Take 41.67 mL of concentrated hydrochloric acid and add a certain amount of deionized water to 500 mL to obtain 1 M hydrochloric acid.

[0054] (2) Cut 2*3 cm copper foam into pieces and ultrasonically clean them in 1 M hydrochloric acid, ethanol, and deionized water for 15 min respectively. Finally, dry them in a vacuum drying oven at 60 °C for later use.

[0055] (3) Weigh 20 g of sodium hydroxide and add it to an appropriate amount of deionized water. After the sodium hydroxide is completely dissolved, transfer the solution to a 500 mL volumetric flask and make up the volume to the 500 mL mark with deionized water to obtain a 1 M sodium hydroxide solution.

[0056] (4) Weigh 0.4564 g of ammonium persulfate, pipette 20 mL of 1 M sodium hydroxide solution and add it to dissolve it by ultrasonication. After dissolution, soak the cleaned copper foam in it for 20 min to obtain blue copper hydroxide.

[0057] (5) Wash the generated copper hydroxide: Wash repeatedly with deionized water. Prepare 20 mL of 0.5 mM aluminum nitrate solution, soak the washed copper hydroxide in the aluminum nitrate solution for 20 min, and then dry the material naturally after soaking.

[0058] (6) Place the dried material on a graphite plate and set the Joule heating program: the voltage is set to 20 V, the current is set to 200 A, the duration is set to 5 s, and the temperature is set to 700 °C. After Joule heating, Al-doped CuO nanosheet material can be obtained.

[0059] Example 5

[0060] (1) Take 41.67 mL of concentrated hydrochloric acid and add a certain amount of deionized water to 500 mL to obtain 1 M hydrochloric acid.

[0061] (2) Cut 2*3 cm copper foam into pieces and ultrasonically clean them in 1 M hydrochloric acid, ethanol, and deionized water for 15 min respectively. Finally, dry them in a vacuum drying oven at 60 °C for later use.

[0062] (3) Weigh 20 g of sodium hydroxide and add it to an appropriate amount of deionized water. After the sodium hydroxide is completely dissolved, transfer the solution to a 500 mL volumetric flask and make up the volume to the 500 mL mark with deionized water to obtain a 1 M sodium hydroxide solution.

[0063] (4) Weigh 0.4564 g of ammonium persulfate, pipette 20 mL of 1 M sodium hydroxide solution and add it to dissolve it by ultrasonication. After dissolution, soak the cleaned copper foam in it for 20 min to obtain blue copper hydroxide.

[0064] (5) Wash the generated copper hydroxide: Wash repeatedly with deionized water. Prepare 20 mL of 0.5 mM aluminum nitrate solution, soak the washed copper hydroxide in the aluminum nitrate solution for 20 min, and then dry the material naturally after soaking.

[0065] (6) Place the dried material on a graphite plate and set the Joule heating program: the voltage is set to 20 V, the current is set to 250 A, the duration is set to 5 s, and the temperature is set to 900 °C. After Joule heating, Al-doped CuO nanosheet material can be obtained.

[0066] Comparative Example 1

[0067] (1) Take 41.67 mL of concentrated hydrochloric acid and add a certain amount of deionized water to 500 mL to obtain 1 M hydrochloric acid.

[0068] (2) Cut 2*3 cm copper foam into pieces and ultrasonically clean them in 1 M hydrochloric acid, ethanol, and deionized water for 15 min respectively. Finally, dry them in a vacuum drying oven at 60 °C for later use.

[0069] (3) Weigh 20 g of sodium hydroxide and add it to an appropriate amount of deionized water. After the sodium hydroxide is completely dissolved, transfer the solution to a 500 mL volumetric flask and make up the volume to the 500 mL mark with deionized water to obtain a 1 M sodium hydroxide solution.

[0070] (4) Weigh 0.4564 g of ammonium persulfate, pipette 20 mL of 1 M sodium hydroxide solution and add it to dissolve it by ultrasonication. After dissolution, soak the cleaned copper foam in it for 20 min to obtain blue copper hydroxide.

[0071] (5) Wash the generated copper hydroxide: wash it repeatedly with deionized water, and then dry it in a vacuum drying oven at 60°C for later use.

[0072] (6) Place the dried material on a graphite plate and set the Joule heating program: the voltage is set to 20 V, the current is set to 250 A, the duration is set to 5 s, and the temperature is set to 800 °C. After Joule heating, the CuO nanosheet material can be obtained.

[0073] Characterization Test

[0074] 1. Main Materials and Methods

[0075] The Al-doped CuO nanosheet electrocatalyst material prepared in Example 2 (see Figure 1 ) were used as test samples and characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and X-ray photoelectron spectroscopy (XPS). The experimental results are as follows: Figure 1 , Figure 2 shown.

[0076] The Al-doped CuO nanosheet electrocatalyst material prepared in Example 2 is shown in FIG. Figure 1 As shown. Figure 1 is the XRD pattern, Figure 2 For SEM images, Figure 3 TEM image. Figure 1 It shows that the catalyst prepared in Example 2 is mainly copper oxide and copper, and the copper peak is mainly attributed to foamed copper. Figure 2 and Figure 3 It can be seen that the morphology of the catalyst is nanosheet flower-like nanoparticles. Figure 4 This is the XPS image of Example 2. Figure 4 (a) is the Cu 2P orbital diagram. Figure 4(b) is the Al 2P orbital diagram. From the Cu2P orbital XPS diagram, it can be seen that the main component of Cu is divalent. A group of satellite characteristic peaks can be observed at 942 eV for divalent copper. At the same time, the Cu 2p 3 / 2 The peak is shifted, and its peak width is greater than the cuprous oxide peak, but it can also be seen from the figure that there is still a small amount of monovalent copper in Cu.

[0077] Determination of electrochemical properties

[0078] 1. Main Materials and Methods

[0079] The Al-doped CuO nanosheet electrocatalyst prepared in Example 2 (see Figure 1 ); wherein the reaction system is carried out in an H-type electrolytic cell. 30 mL of 1M NaOH solution is added to the anode, and 30 mL of a mixed solution of NaOH and NaN03 (the concentration of NaOH is 1 mol / L, and the concentration of NaN03 is 0.1 mol / L) is added to the cathode. NaN03 is used as a nitrogen source, and the two electrodes are separated by a Nafion proton exchange membrane. The working electrode is the prepared catalyst, the reference electrode is a mercury / mercury oxide electrode, and the counter electrode is a platinum sheet electrode.

[0080] (1) Current density test

[0081] The Al-doped CuO nanosheet catalyst and CuO catalyst prepared in Example 2 and Comparative 1 were used as working electrodes, respectively, and linear sweep voltammetry (LSV) was used for testing. The scanning interval was 0.2~-1 V (relative to standard hydrogen electrode) and the scanning rate was 10 mV / s. The experimental results are shown in FIG. Figure 5 shown. Figure 5 This is a comparison curve of Al-CuO and CuO lsv. It can be seen from the figure that the current density of the Al-doped CuO nanosheet electrocatalyst prepared in Example 2 is significantly improved compared with the CuO catalyst not doped with Al, indicating that the catalyst prepared by Al doping has better electrochemical properties and the current density has reached the ampere level.

[0082] (2) Faraday efficiency and yield test of electrocatalytic nitrate reduction reaction

[0083] The Al-doped CuO nanosheet electrocatalyst prepared in Example 2 was used as the working electrode, and the yield was determined by constant potential method. The working potential was set to -1.2 V, -1.3 V, -1.4 V, -1.5 V and -1.6 V (relative to mercury / mercuric oxide reference electrode), and the power was continuously turned on for 0.5 h. After the reaction was completed, the electrolyte was collected, and the concentration of ammonia was quantitatively analyzed by ultraviolet-visible spectrophotometer to calculate the yield of ammonia and the Faraday efficiency of nitrate. The calculation formula is as follows:

[0084] FE(NH3) = n × F × C(NH4 + ) × V / (M × Q) × 100 %

[0085] Where F refers to: Faraday constant (96485 C mol -1 ); M is the molecular mass of NH3 (17 g mol -1 ); Q is the amount of electricity passing through the electrode (C); n is the number of electrons consumed by nitrate to ammonia, which is 8;

[0086] r(NH3) = C(NH4 + ) × V / (t × S cat )

[0087] Where r(NH3) is used to represent the ammonia yield (μg h -1 cm -2 ); t represents the reaction time (h); S cat represents the catalyst loading (cm -2 ); C(NH4 + ) refers to the ammonia concentration in the reaction product (μg mL -1 ); V refers to the volume of the cathode electrolyte (30 mL). The experimental results are shown in Figure 6 shown.

[0088] Figure 6 The Faraday efficiency and ammonia yield of Al-doped CuO nanosheet electrocatalysts are shown in Figure 2. The experimental results show that in 0.1 mol / L N03 - In alkaline solution, the best performance is achieved at -0.635 V vs. RHE, achieving a Faradaic efficiency of 95.7% and a charge / discharge rate of about 60 mg h -1 cm -2 ammonia yield.

[0089]

[0090] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field, within the technical scope disclosed by the present invention, shall make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention, which shall be covered within the protection scope of the present invention. The technicians in the relevant technical field shall understand that any improvement of the present invention, the equivalent replacement of the raw materials selected by the present invention, the replacement and selection of auxiliary components, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing Al-doped CuO nanosheet electrocatalyst, characterized in that: The steps include: (1) Cleaning foam copper; (2) soaking the cleaned copper foam in a mixed solution of sodium hydroxide and ammonium persulfate to obtain copper hydroxide, rinsing it with deionized water, and drying it in a vacuum oven for later use; (3) soaking the obtained copper hydroxide in an aluminum salt solution and drying it naturally after soaking; (4) The dried material is placed on a graphite plate and heated by a Joule heating program to obtain an Al-doped CuO nanosheet catalyst.

2. The method for preparing an Al-doped CuO nanosheet electrocatalyst according to claim 1, characterized in that: The process of cleaning the copper foam in step (1) is: immersing the copper foam in a dilute hydrochloric acid solution, ethanol and deionized water for ultrasonic cleaning.

3. The method for preparing an Al-doped CuO nanosheet electrocatalyst according to claim 2, characterized in that: The concentration of the dilute hydrochloric acid solution is 1-2 mol L -1 , the ultrasonic time is 15-20 min.

4. The method for preparing an Al-doped CuO nanosheet electrocatalyst according to claim 1, characterized in that: In the step (2), the concentration of sodium hydroxide in the mixed solution of sodium hydroxide and ammonium persulfate is 1 mol L -1 The concentration of ammonium persulfate is 0.1 mol L -1 .

5. The method for preparing an Al-doped CuO nanosheet electrocatalyst according to claim 1, characterized in that: In the step (2), the copper foam is immersed in the mixed solution of sodium hydroxide and ammonium persulfate for 15-30 minutes.

6. The method for preparing an Al-doped CuO nanosheet catalyst according to claim 1, characterized in that: The aluminum salt solution is a solution of aluminum nitrate, aluminum sulfate, aluminum chloride or aluminum oxide.

7. The method for preparing an Al-doped CuO nanosheet catalyst according to claim 6, characterized in that: The concentration of the aluminum salt solution is 0.4-0.6 mM, and the immersion time is 10-30 min.

8. The method for preparing an Al-doped CuO nanosheet catalyst according to claim 1, characterized in that: The Joule heating program is as follows: the voltage is set to 20 V, the current is set to 200 A-250 A, the duration is 3-8 s, and the temperature is set to 700°C-900°C.

9. An Al-doped CuO nanosheet catalyst, characterized in that: The catalyst is prepared by the preparation method described in any one of claims 1 to 8.

10. The use of an Al-doped CuO nanosheet catalyst according to claim 9, characterized in that: The catalyst is used for electrocatalytic nitrate reduction to synthesize ammonia.

Citation Information

Patent Citations

  • Preparation of aluminum-doped copper oxide electrocatalyst and application of aluminum-doped copper oxide electrocatalyst in electrocatalysis of CO2 reduction

    CN118186471A

  • Copper electrocatalyst for producing ammonia by electrochemically reducing nitrate and preparation method of copper electrocatalyst

    CN118910652A

  • Transition metal doped copper micron wire catalyst and preparation method and biomass reduction application thereof

    CN119352089A

  • Metal-loaded three-dimensional copper-based catalyst as well as preparation method and application thereof

    CN119352092A

  • Method for rapidly synthesizing self-supporting high-entropy alloy difunctional electrocatalyst by Joule heat

    CN119465285A